Bio-products market in Georgia: current challenges and development perspectives. (5th May 2020) - Natsvlishvili, Ia; Kharaishvili, Eteri; Lazariashvili, Tamar
The article explores the organic food market in the world and in Georgia. The growth tendency of demand for bio-products is assessed. For Georgia, bio-production is considered as an alternative to the traditional system of agricultural production. The paper examines the experience of European countries. The ways for development of production of bio-products in Georgia are identified by comparative analysis; opportunities for population employment and income growth, nutrition quality, and environmental improvement are substantiated through the development of bio-production. The authors have studied the state programs for production of bio-products and sales promotion; conclusions were made on the feasibility of implementing adapted programs in Georgia. Qualitative research was carried out in order to identify the problems and directions of development in the field of bio-production and bio-market development; through the impact and urgency matrix were identified the barriers to bio-production, drawn conclusions on the identified problems and proposed appropriate recommendations.